Desvelando os processos de escolarização de alunos surdos no cenário da EJA : um estudo de caso - Rocha, Marcos Leite (2012)
The discussions presented in this study concern the interface between Special Education and Education for Youth and Adults (EJA). It particularly investigates the schooling processes of deaf students enrolled in regular classes of EJA at an elementary school of the Municipal Education System in the City of Vitória, ES, Brazil. Since the 1980s, the school has been a unique space for deaf students because it gives professional users of Brazilian Sign Language (LIBRAS) the opportunity to both translate/interpret the classes and provide special education assistance. In order to base our discussion, we adopted a set of studies and papers on Special Education and Education for Youth and Adults enrolled in conventional classrooms, linked to propositions of Sociology of Absences and Sociology of Emergencies by Boaventura de Souza Santos. For building and systematizing the data in the research field, ethnography was used. The study is organized in six chapters, which together show the place for the researcher/ s discourse, the theoretical concepts adopted in the study; the methodological history of research, the education policy for death people implemented in the municipality of Vitória; the routine of the school investigated. The results point to the importance of analyzing the interface of Special Education in Education for Youth and Adults so that the schooling processes of deaf young and adult students in regular EJA classrooms in the City of Vitoria are discussed; and to the need of considering alternatives that provide deaf young and adult students with the services and support established by the national and local bilingual education policy from the school inclusion perspective